Glomerular Renal Failure (quantitative evaluation and functional interrelationships) - Monge Cassinelli, Carlos (1959)
The study of the failure of such a complex organ such as the kidney, raises the difficulty of reducing to a few multiple physiological variables to the unit and quantitative assessment of the phenomena that occur simultaneously in the course of normal or pathological functioning .